Lithium Lanthanum Titanate derived from Lanthanum Oxalate as the Anode Active Material in Lithium-ion Batteries - Ma'dika, Benediktus; Pravitasari, Retna Deca; Tasomara, Riesma; Hapsari, Ade Utami; Damisih; Rahayu, Sri; Yuliani, Hanif; Arjasa, Oka Pradipta; Herdianto, Nendar; Deni, Yelvia; Suyanti; Syahrial, Anne Zulfia; et al. (International Journal of Integrated Engineering, 2022)
Lithium-ion battery has been drawing attention from researchers due to its excellent properties in terms of electrochemical and structural stabilities, low cost, and high safety feature, leading to prospective applications in electric vehicles and other large-scale applications. However, lithium-ion batteries are still in charging time owing to its low conductivity, restricting its wide applications in large-scale applications. In this work, therefore, lithium lanthanum titanate (LLTO) was synthesized derived from lanthanum oxalate, as a lanthanum source, for an anode active material application in the lithium-ion batteries due its high electrochemical conductivity and pseudocapacitive characteristics. To the best our knowledge, our work is the first one to synthesize LLTO from lanthanum oxalate as the lanthanum source. Commercial lithium carbonate and commercial titanium oxide were used as the lithium and titanium sources, respectively. We used the low cost and simple solid-state reaction process to synthesize this material and performed a two-step calcination processs at 800 oC for 8 hours and 1050 oC for 12 hours under ambient atmosphere. The physical characteristics showed that LLTO possesses high purity (98.141%) and micro sized grains with abundant empty spaces between the grains. This, therefore, lead to improved electrochemical performances such as stable discharge capacity at low potential even near to zero (98.67 mAh), and a high conductivity of 2.45 Ã— 10-2 S/cm at room temperature. This LLTO is interesting to be used as the anode active material in low potential lithium-ion battery applications.